Diagnostic accuracy of 18F-FDG-PET in abdominal sepsis in rats - Azevedo,Ítalo Medeiros (2020)
Abstract Purpose The objective of this study was to investigate the accuracy of 18F-FDG-PET in the diagnosis of multibacterial abdominal sepsis by cecum ligation and puncture (CLP) in rats. Methods Adult Wistar rats ( Rattus norvegicus ), weighing 227±35g, were allocated into a sepsis group by CLP (n=10) and sham group (n=10). 18F-FDG-PET using microPET was performed on all rats after 24 hours. Results All animals survived for postoperative 24h. The abdomen/liver ratio of the standardized uptake value (SUV) percentage was significantly higher in the sepsis group than in the sham (p=0.004). The ROC curve showed an accuracy of 18F-FDG-PET to detect abdominal sepsis of 88.9% (p=0.001), sensitivity of 90% and specificity of 88.9%. When a cut-off point of 79% of the ratio between the SUV on the abdominal region and liver was established, the sensitivity was 90%, specificity of 88.9%; positive and negative predictive values of 90.0% and 88.9%, respectively. Conclusions The diagnostic accuracy of 18F-FDG-PET in rats with abdominal sepsis was significantly high. It was also demonstrated the predictive ability of the abdomen/liver SUV ratio to diagnose abdominal sepsis. These findings may have implications for the clinical setting, locating septic foci with PETscan.